Examining Inclusive Education Policies of Nepal: A Comprehensive Review Analysis - Acharya, Bisna; Sigdel, Surya (Nepalese Journal of Development and Rural Studies, 2023)
This study seeks to interpret inclusive education policies in Nepal to ensure they align with constitutional rights, particularly for individuals with diverse learning needs. Nepal has conducted a thorough evaluation of its inclusive education policies. An analytical research approach has been used to analyze the policy provisions that protect constitutional education rights. Every child in Nepal is entitled to receive a fundamental education according to the constitution established in 2015. This study provides a comprehensive analysis of the acts, policies, and educational documents that were relevant to the study. The findings highlight the successes and challenges of Nepal’s inclusive education policy. The study also explores the connection between constitutional rights and practical scenarios, while highlighting the importance of considering cultural and socio-economic factors for fostering inclusivity. Improving inclusive education policies involves recognizing and building upon strengths while also addressing areas for improvement. This study intend to harmonize constitutional ideals and educational practices to provide insights for policy changes and foster inclusive and equitable education in Nepal and beyond.